Experimental modelling and human data of glottal area declination rate for vowel and semi-occluded vocal tract phonation. (April 2021) - Horáček, Jaromír; Radolf, Vojtěch; Bula, Vítězslav; Laukkanen, Anne-Maria
Highlights: Glottal closing velocity has been used as an estimate of impact stress in phonation. Phonation in model and in human were compared for vowel and phonation through a tube with distal end in air or in water. Glottal area waveform was studied with high-speed imaging. MADR is not a reliable estimate of impact stress; instead, maximum velocity before closure needs to be studied. Abstract: Objective: The aim of this study was to investigate how the maximum area declination rate ( MADR ) of the glottis corresponds to the maximum velocity of the self-oscillating vocal folds just before their collision. The maximum velocity before collision is closely related to impact stress in the colliding vocal folds and, thus, it is an important indicator of vocal loading. Methods: High speed imaging data for a male subject and measurements of the glottal area waveforms performed on a physical 1:1 scaled model for phonation on vowel [u:] were compared with those obtained during a semi-occluded vocal tract which increases voice source-vocal tract interaction. Semi-occlusion was obtained by phonation through a glass resonance tube with the distal end in air or submerged 10 cm in water. Results: The results show that the area declination rate of the glottis, i.e., closing velocity, before the glottal closure is substantially lower than the MADR, and also lower in semi-occluded vocal tract phonation through a tube into air and into water than in vowel phonation. Conclusions: The results suggest that MADR is not a reliable estimate of impact stress, and that impact stress in tube therapy is lower than in vowel phonation.